2008
DOI: 10.1161/circresaha.108.175174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Enhancement of Stem Cell Engraftment, Survival, and Efficacy

Abstract: Abstract-Cell-based therapies for the prevention and treatment of cardiac dysfunction offer the potential to significantly modulate cardiac function and improve outcomes in patients with cardiovascular disease. To date several clinical studies have suggested the potential efficacy of several different stem cell types; however, the benefits seen in clinical trials have been inconsistent and modest. In parallel, preclinical studies have identified key events in the process of cell-based myocardial repair, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 112 publications
2
103
0
Order By: Relevance
“…1 However, clinical trials of stem cell therapy have shown a slight improvement of cardiac function, and if some improvement was observed, it is now thought to be attributable to paracrine effects but not transdifferentiation of transplanted stem cells into cardiomyocytes of transplanted cells. 2 The major obstacles to current stem cell therapy are as follows. First, the efficiency of cardiomyocyte differentiation of cultured and transplanted stem cells is quite low.…”
Section: Editorial P 2555mentioning
confidence: 99%
“…1 However, clinical trials of stem cell therapy have shown a slight improvement of cardiac function, and if some improvement was observed, it is now thought to be attributable to paracrine effects but not transdifferentiation of transplanted stem cells into cardiomyocytes of transplanted cells. 2 The major obstacles to current stem cell therapy are as follows. First, the efficiency of cardiomyocyte differentiation of cultured and transplanted stem cells is quite low.…”
Section: Editorial P 2555mentioning
confidence: 99%
“…77 Gene therapy currently lacks precise quantitative control of expression, but some applications may tolerate broad ranges of overexpression. Biomaterials can sustain delivery, protect plasmid DNA from degradation, and increase transfection efficiency.…”
Section: Gene Deliverymentioning
confidence: 99%
“…How to improve the survival of grafted MSCs is a demanding task for further research. [3][4][5] One strategy is to manipulate the expression of key genes involved in the cell survival. In the previous studies, genetic modification of MSCs overexpressing some pro-survival genes, such as Akt, Bcl-2, stromal-derived factor 1 (SDF-1), and chemokine (c-c motif) receptor-1, had been tested to improve the survival of grafted cells in vivo but with little efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, genetic modification of MSCs overexpressing some pro-survival genes, such as Akt, Bcl-2, stromal-derived factor 1 (SDF-1), and chemokine (c-c motif) receptor-1, had been tested to improve the survival of grafted cells in vivo but with little efficacy. 3,6 Small interfering RNA (siRNA)-mediated silencing of oxidative injuryrelated gene expression may open a novel possibility for enhancing cell survival. As an oxygen-dependent gene, the prolyl hydroxylase domain protein 2 (PHD2) gene regulates hypoxia-inducible factor-1α (HIF-1α) and nuclear factor-κB (NF-κB), which submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%